The Impact of Entrepreneurship Education on Sociopreneurship Intention: The Moderating Role of Past Experience - Anggraeni, Salsabila Fitria; Kurjono, K; Mulyani, Heni (Proceedings International Conference on Education Innovation and Social Science, 2025)
The increasing prevalence of social issues, such as poverty, environmental degradation, and inequality, highlights the urgent need for innovative solutions that combine economic and social value creation. Sociopreneurship has emerged as a promising approach to addressing these challenges. However, preliminary surveys indicate that university students' sociopreneurship intention remains low, despite their exposure to entrepreneurship education. This study investigates the influence of entrepreneurship education and self-efficacy on sociopreneurship intention, with past experience as a moderating variable. Using a quantitative approach, data were collected from students of FPMIPA, FPIPS, and FPEB at Universitas Pendidikan Indonesia who had completed entrepreneurship courses and participated in social organizations. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that both entrepreneurship education positively and significantly affect sociopreneurship intention. Furthermore, past experience significantly moderates the relationship between entrepreneurship education and sociopreneurship intention, indicating that relevant experiences can enhance the educational impact. These results emphasize the importance of integrating experiential learning into entrepreneurship curricula to strengthen students’ readiness and motivation to become sociopreneurs.